Clusterin knockdown has effects on intracellular and secreted von Willebrand factor in human umbilical vein endothelial cells. - Allaura A Cox; Alice Liu; Christopher J Ng (PLoS ONE)
Alterations in von Willebrand factor (VWF) have an important role in human health and disease. Deficiency of VWF is associated with symptoms of bleeding and excesses of VWF are associated with thrombotic outcomes. Understanding the mechanisms that drive VWF regulation can lead to a better understanding of modulation of VWF levels in humans. We identified clusterin (CLU) as a potential candidate regulator of VWF based on a single cell RNA sequencing (scRNA-seq) analysis in control endothelial cells (ECs) and von Willebrand disease (VWD) endothelial colony-forming-cells (ECFCs). We found that patients with deficiencies of VWF (von Willebrand disease, VWD) had decreased CLU expression and ECs with low VWF expression also had low CLU expression. Based on these findings, we sought to evaluate the role of CLU in the regulation of VWF, specifically as it relates to VWD. As CLU is primarily thought to be a golgi protein involved in protein chaperoning, we hypothesized that knockdown of CLU would lead to decreases in VWF and alterations in Weibel-Palade bodies (WPBs). We used both siRNA- and CRISPR-Cas9-based approaches to modulate CLU in human umbilical vein endothelial cells (HUVECs) and evaluated VWF protein levels, VWF mRNA copy number, and WPB quantity and size. We demonstrated that siRNA-based knockdown of CLU resulted in decreases in VWF content in cellular lysates and supernatants, but no significant change in WPB quantity or size. A CRISPR-Cas9-based knockdown of CLU demonstrated similar findings of decreases in intracellular VWF content but no significant change in WPB quantity or size. Our data suggests that CLU knockdown is associated with decreases in cellular VWF content but does not affect VWF mRNA levels or WPB quantity or size.